Youth and Prayer in a Secular Age - Ellis, Wesley W. (Journal of youth and theology, 2025)
This article diagnoses the difficulty of prayer for young people inhabiting a secular society and offers the beginnings of a theology of prayer for this context. For young people in the United States, our secular age is defined by immanence, excessive positivity, and dynamic stabilization that constitute anxiety as a primary motivator that leads to burnout and exhaustion. Prayer as communion with God offers a corrective that can relieve anxiety and offer renewal. For this, prayer must not be thought primarily as a human action, but a divine action. In prayer, we do not grasp God, we are grasped by God. As such, prayer is a grace young people need, and its teaching must become the primary pastoral vocation in a secular age.